Authentication of the therapeutic Lamiaceae taxa by using pollen traits observed under scanning electron microscopy. Issue 6 (24th January 2022) - Bahadur, Saraj; Taj, Sehrish; Ahmad, Mushtaq; Zafar, Muhammad; Gul, Saba; Shuaib, Muhammad; Butt, Maryam Akram; Hanif, Uzma; Nizamani, Mir Muhammad; Hussain, Fida; Romman, Muhammad
Abstract: Herbal medicines are gaining popularity worldwide for human healthcare because of their therapeutic potential. However, adulteration and use of unauthentic raw herbals as substitutes have become a major issue for the local communities and industry for reasons of safety and efficacy. Therefore, the authentication of medicinal plants before their use in herbal medicines is a need of time. Hence, the present study was designed with an aim, to authenticate the therapeutic Lamiaceous taxa by using pollen traits observed under scanning electron microscopy. Pollen micro‐morphological studies solve the problem through discrimination and correct identification of the Lamiaceae species from the adulterants. Based on pollen features, Lamiaceae were further divided into two sub‐families Lamioideae (tricolpate) and Nepetoideae (hexa‐colpate). The pollen grains of Lamioideae were found as small to medium‐sized, tricolpate, radially/bilateral symmetrical, sub‐spheroidal and oblate shape. Besides, exine patterns bireticulate, reticulate and micro‐reticulate, colpus surface sculpturing as psilate, gemmate, scabrate, and verrucate have also been reported. A significant variation was found in the pattern of the reticulum, thickness, and the number of secondary lumina per primary lumen. Similarly, Nepetoideae has a hexa zono‐colpate pollen but tri and tetra zono‐colpate pollen have also been observed. Hence, this study contributes to the authentication and correct identification of medicinally important Lamiaceae taxa by using scanning electron microscopic techniques and can help to solve the adulteration problem. Highlights Authentication of medicinally important Lamiceous taxa was carried out through scanning electron microscopic techniques. Chemotaxonomic characterization was used for the accurate identification of the therapeutic taxa. The medicinal, palynological and phytochemical significance of Lamiaceae taxa were evaluated. A significant variation was seen in the palynological traits that help in the determination and authentication of the therapeutic Lamiaceous species. Based on the chemotaxonomic characterization, our study can help to solve the adulteration problem for the reason of safety and efficacy. Abstract :